Experiences of new family physicians finding jobs with obstetrical care in the USA. Issue 3 (14th June 2019) - Eden, Aimee R; Barreto, Tyler; Hansen, Elizabeth Rose
Abstract : Objective: This study aimed to explore how new family medicine graduates who want to include obstetrics in their scope of practice identify and select jobs and to understand how employment influences scope of practice in family medicine, particularly the ability to provide maternity care and deliver babies. Design: Mixed-methods study including a survey and qualitative interviews conducted in 2017. Setting: We electronically surveyed US family physicians and followed up with a purposeful subsample of these physicians to conduct in-depth, semistructured telephone interviews. Participants: 1016 US family medicine residency graduates 2014–2016 who indicated that they intended to deliver babies in practice completed a survey; 56 of these were interviewed. Main outcome measures: The survey measured the reasons for not doing obstetrics as a family physician. To identify themes regarding finding family medicine jobs with obstetrics, we used a team-based, immersion–crystallisation approach to analyse the transcribed qualitative interviews. Results: Survey results (49% response rate) showed that not finding a job that included obstetrics was the primary reason newly graduated family physicians who intended to do obstetrics were not doing so. Qualitative interviews revealed that family physicians often find jobs with obstetrics through connections or recruitment efforts and make job decisions based on personal considerations such as included geographical preferences, family obligations and lifestyle. However, job-seeking and job-taking decisions are constrained by employment-related issues such as job structure, practice characteristics and lack of availability of family medicine jobs with obstetrics. Conclusions: While personal reasons drove job selection for most physicians, their choices were constrained by multiple factors beyond their control, particularly availability of family medicine jobs allowing obstetrics. The shift from physician as practice owner to physician as employee in the USA has implications for job-seeking behaviours of newly graduating medical residents as well as for access to healthcare services by patients; understanding how employment influences scope of practice in family medicine can provide insight into how to support family physicians to maintain the scope of practice they desire and are trained to provide, thus, ensuring that families have access to care.